On Complementary Root Locus of Biproper Transfer Functions - Teixeira, Marcelo C. M. [UNESP]; Assuncao, Edvaldo [UNESP]; Cardim, Rodrigo [UNESP]; Silva, Neusa A. P. [UNESP]; Machado, Erica R. M. D. [UNESP] (Hindawi Publishing Corporation, 2009)
This paper addresses the root locus (locus of positive gain) and the complementary root locus (locus of negative gain) of biproper transfer functions (transfer functions with the same number of poles and zeros). It is shown that the root locus and complementary root locus of a biproper transfer function can be directly obtained from the plot of a suitable strictly proper transfer function (transfer function with more poles than zeros). There exists a lack of sources on the complementary root locus plots. The proposed procedure avoids the problems pointed out by Eydgahi and Ghavamzadeh, is a new method to plot complementary root locus of biproper transfer functions, and offers a better comprehension on this subject. It also extends to biproper open-loop transfer functions, previous results about the exact plot of the complementary root locus using only the well-known root locus rules. Copyright (C) 2009 Marcelo C. M. Teixeira et al.